2013
DOI: 10.1038/modpathol.2012.163
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal micropapillary carcinomas are associated with poor prognosis and enriched in markers of stem cells

Abstract: Colorectal micropapillary carcinoma has recently been reported as an aggressive variant of adenocarcinoma with a high incidence of lymph node metastasis, but has not been well investigated in terms of survival analysis. This study analyzed the clinicopathological characteristics, including survival data, of the patients with micropapillary carcinoma. We hypothesized that the aggressive features of micropapillary carcinoma might be related to the presence of more tumor cells with stem cell phenotype in colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 51 publications
2
46
1
Order By: Relevance
“…Higher expression of Notch3 is associated with increased tumor growth rate, and knocking it down slows tumor growth . Notch3 expression is significantly higher in micropapillary carcinomas compared with nonmicropapillary carcinomas (69 vs. 42%), with micropapillary carcinomas having more frequent lymphovascular invasion, higher tumor stage, and LN metastasis rate . Thirty‐eight percent of stage II and III colorectal cancers overexpressed Notch3, which was correlated with higher tumor grades, higher rates of venous invasion and LN metastasis, and shorter recurrence‐free survival .…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Higher expression of Notch3 is associated with increased tumor growth rate, and knocking it down slows tumor growth . Notch3 expression is significantly higher in micropapillary carcinomas compared with nonmicropapillary carcinomas (69 vs. 42%), with micropapillary carcinomas having more frequent lymphovascular invasion, higher tumor stage, and LN metastasis rate . Thirty‐eight percent of stage II and III colorectal cancers overexpressed Notch3, which was correlated with higher tumor grades, higher rates of venous invasion and LN metastasis, and shorter recurrence‐free survival .…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Alternative splicing of exons 6-15 (variant exons 1-10) gives rise to numerous variant forms of CD44 (CD44v), in which an additional segment encoded by one or more of the variant exons is inserted in the extracellular domain of CD44s, which is encoded by exons 1-5 and exons 16-20 (16,42,43). The variant 6 isoform (CD44v6), in particular, is associated with several cancer types but not in somatic cells (15,(18)(19)(20)(21). Moreover, CD44v6 is widely known as a marker of CSCs (18,21,36,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the importance of SOX2 in cancer metastasis has also been addressed. Previously, several studies demonstrated that SOX2 expression was closely associated with lymph node metastasis, distant spread and poor prognosis in colorectal carcinoma patients (6,90,91). Certain data suggested that SOX2 knockdown may induce mesenchymal-epithelial transition (MET).…”
Section: Association Between Sox2 and Lymph Node Metastasismentioning
confidence: 99%